THE PROCESS OF INSTITUTIONALIZATION OF THE CITIZENSHIP TERRITORIES IN THE STATE OF SAO PAULO - Souza, Sergio Pereira de; Hespanhol, Rosangela Ap de Medeiros [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2016)
The article analyze the process of institutionalization of the Territorios da Cidadania (TC) in Sao Paulo State, highlighting the procedures and criteria adopted for the implementation of this program and the socioeconomic characteristics of the TC Pontal do Paranapanema, Vale do Ribeira and Sudoeste Paulista. To achieve the objective outlined in the article were used as instruments: literature; collection and systematization of data Territorial Matrix 2013, available on the website (PTC); and interviews with regional program managers. The institutionalization of TC presupposes greater participation of the Federal Government in the direction of Brazilian public policy, aiming to universalize citizenship programs, reduce poverty and implement infrastructure, equipment and services, through a mix of projects for the low economic dynamism territories. The municipalities of the TC became focus for action of the Federal Government, and government action establishing planning areas for greater social and spatial control set based on a sectoral and punctual logic.
Keywords: Territorial Development; Territorios da Cidadania; Pontal do Paranapanema; Vale do Ribeira; Southwestern of Sao Paulo